Effect of Azadirachta indica crude bark extracts concentrations against gram-positive and gram-negative bacterial pathogens - Shreelakshmidevi Singaravelu; Jaikumar Sankarapillai; Abilash Sasidharn Chandrakumari; Pammy Sinha (Wolters Kluwer Medknow Publications, 2019)
Background: Today's pharmaceutical markets are crowded with antibacterial agents, yet their toxicities and resistance are always contentious. Azadirachta indica is used in India as an age-old treatment for diverse medical conditions. This study was put forth to analyze the antibacterial action of A. indica bark extract on different bacterial pathogens. Materials and Methods: A. indica bark extract was prepared using Soxhlet extraction method. The bark extract of A. indica was screened for antibacterial activity by agar well diffusion assay technique against Staphylococcus aureus, Enterococcus faecalis, Pseudomonas aeruginosa, and Proteus mirabilis. Ciprofloxacin (5 µg per disc) was used as positive control. All assays were carried out under strict aseptic precautions. All the concentrations included were duplicated, and the results obtained were the average of two independent experiments. Broth microdilution method was used to study the minimum inhibitory concentration of the bark extract of A. indica. Results: A. indica bark extract has shown antibacterial activity against all concentrations of bark extract, whereas antibacterial activity against S. aureus was observed at higher concentration of >500 µg/mL. The bark extract of A. indica showed zone of clearance against E. faecalis, P. aeruginosa, and P. mirabilis at all concentrations. Zone of inhibition was observed in higher concentrations against S. aureus. Conclusion: This study has shown that A. indica bark extract has a potent antibacterial property against S. aureus, E. faecalis, P. aeruginosa, and P. mirabilis. Further isolation of bioactive compounds may lead to a new scope in the treatment of bacterial infections.